2012
DOI: 10.1116/1.3692753
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of electrical and optical properties of molybdenum oxide thin films by ultralow pressure sputtering method

Abstract: In this work, we investigated the structural, electrical and optical properties of molybdenum oxide thin films deposited by the reactive dc magnetron sputtering method. The molybdenum oxide films were prepared at sputtering pressures ranging from 6.7 × 10−1 to 6.7 × 10−2 Pa. In order to promote their electrical conductivity, all the deposited MoOx films were annealed in Ar ambient at 450 °C for 8 h. The resistivity of the MoOx films varied from 10−4 to 10−2 Ω cm depending on the O2 content in the sputtering am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…Since the argon pressure was kept constant at 2.44 Â 10 À3 mbar during all depositions, it is likely that the oxygen causes target poisoning and therefore reduces the deposition rate. 7 In this regime though, MoO x molecules are sputtered off instead of metallic Mo. The filmgrowth rate increases directly with the applied power in the DC sputtering process, which is in agreement with observations reported in the literature.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Since the argon pressure was kept constant at 2.44 Â 10 À3 mbar during all depositions, it is likely that the oxygen causes target poisoning and therefore reduces the deposition rate. 7 In this regime though, MoO x molecules are sputtered off instead of metallic Mo. The filmgrowth rate increases directly with the applied power in the DC sputtering process, which is in agreement with observations reported in the literature.…”
supporting
confidence: 90%
“…In their work, polycrystalline films were observed independently of the oxygen partial pressure, and in addition, an increase in surface roughness with the oxygen partial pressure was also reported. In the case of as-deposited films formed at room temperature, Oh et al 7 also found amorphous films at similar sputtering pressures as presented here, and they, in addition, reported on poly-crystalline films formed at ultra low sputtering pressures. In this work, non-crystalline films are observed independently of the oxygen partial pressures in the range of 1.00 Â 10 À3 to 3.00 Â 10 À3 mbar.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Among these metal oxides, MoO 3 shows one of the largest work functions, ,, combined with relatively low deposition temperatures, which makes it an attractive material for device integration. In addition, as in the case for other transition metal oxides, the electrical, optical, and physical properties of MoO x can be tuned over wide ranges via defect engineering, making MoO x particularly interesting for various optoelectronic device applications.…”
Section: Introductionmentioning
confidence: 99%